Human Security and the Relocation of Internally Displaced Environmental Refugees in Cameroon. (31st July 2017) - Buchenrieder, Gertrud; Mack, Christina; Balgah, Azibo Roland
Abstract: The more frequent occurrence of natural disasters due to climate change will doubtlessly blow up the number of environmental refugees, not the least in sub-Saharan Africa. Not all of them flee their countries, many being internally displaced. Ideally, abandonment of the homelands is not permanent. In order to improve our understanding of internally displaced environmental refugees and the framing conditions to either return or not, this contribution uses the human security concept of the United Nations to construct a unique micro-level human security index, consisting of seven dimensions. The human security index is employed on a sample of environmental refugees, who became internally displaced in 1986 during the Lake Nyos natural disaster in Cameroon. A number of these households has decided to return, although legally prohibited. The majority is still in the resettlement camps, waiting to return. Binominal logit analysis of actual and potential return behaviour in relation to the human security index revealed, among others that health security is a self-selection variable, increasing the odds of returning. The perception of self-efficacy may be important here. A major incentive for returnee households is the potentially higher economic security due to the meanwhile improved agro-ecological situation in the homelands.